2023
DOI: 10.3390/foods12030479
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Functional Characterization Reveal That Peclg Gene Contributes to the Virulence of Penicillium expansum on Apple Fruits

Abstract: Penicillium expansum is the causal agent of blue mold decay on apple fruits and is also known to be the major producer of patulin, a mycotoxin that represents serious hazard to human health. Several mechanisms have been suggested to explain the pathogenesis of P. expansum in host plants. Secreted effector proteins are vital for the pathogenicity of many fungal pathogens through manipulating their hosts for efficient colonization. In this study, we performed a RNA-Seq analysis followed by computational predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recent work in P. expansum, a concanavalin A-like lectin/glucanase (PeCLG) lacking a mutant strain, showed several abnormalities concerning vegetative growth or development, including reduced conidia production and germination. 32 These data demonstrated the involvement of AwEGH in fungal growth and development. However, the roles of AwEGH and its homologues might regulate the fungal growth and development in a species-dependent manner, and further experiments are required to reveal the potential intrinsic mechanisms associated with this regulation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recent work in P. expansum, a concanavalin A-like lectin/glucanase (PeCLG) lacking a mutant strain, showed several abnormalities concerning vegetative growth or development, including reduced conidia production and germination. 32 These data demonstrated the involvement of AwEGH in fungal growth and development. However, the roles of AwEGH and its homologues might regulate the fungal growth and development in a species-dependent manner, and further experiments are required to reveal the potential intrinsic mechanisms associated with this regulation.…”
Section: Discussionmentioning
confidence: 69%
“…Recent work in P. expansum, a concanavalin A-like lectin/glucanase ( PeCLG ) lacking a mutant strain, showed several abnormalities concerning vegetative growth or development, including reduced conidia production and germination . These data demonstrated the involvement of AwEGH in fungal growth and development.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, among the effectors there is a large proportion that correspond to genes for enzymes that degrade the cell wall, which include lectins/glucanases similar to concanavalin A, pectin lyase and pectinesterase. A new effector gene, Peclg, has been identified and showed that it is relevant in conidiation, germination and environmental stress response [ 37 ]. Interestedly, in this study this group is also represented by an endoglucanase (PEX1_094750) and by another Glycoside hydrolase of family 12 that could have similarity with Concanavalin A-like lectins/glucanases (PEX1_081540).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2022) found that nine transcription factors were closely related to pears being infected with P. expansum [15]. A large number of genes, such as PeRacA, PeRmtC, PeSCP, PeSntB, PeNIP, PeNox, PeSet1, PeLae, PeVeA, PeCreA, PeLysMs, PeNLPs, and PePRT, were also proven to be critical to the virulence of P. expansum [16][17][18][19][20][21][22][23]. In addition, the biosynthesis pathway of patulin, which is the most important secondary metabolite of P. expansum and poses severe genotoxicity and cytotoxicity to animals and humans, has been systematically dissected at the molecular and biochemical level [1,24,25].…”
Section: Introductionmentioning
confidence: 99%